In vitro clonal propagation of Dieffenbachia sp. I. initial studies on sterilization of explants and selection of culture media - Atienza, Sharon Mae D. (2000)
Stem disc explants of Dieffenbachia sp. were subjected to different Clorox concentrations ranging from 5 to 15% for 10 to 20 minutes. Results showed that the most effective treatment was 10% Clorox for 15 minutes. A modified Murashige and Skoog medium containing (a) 1 mg/l benzylaminopurine (BA), (b) 0.1 mg/l naphthaleneacetic acid (NAA) + 2.5 mg/l BA, or (c) 0.2 mg/l BA was used. No shoots were observed indicating that a much longer time is needed for shoot induction. Other factors such as plant growth regulator (PGR) combinations and age of explant can also affect shoot emergence. Whether the proper concentration of PGRs in the medium is achieved should also be taken into account
Thesis (BS Biology) -- University of the Philippines Mindanao, 2000